Salivary uric acid as a non-invasive marker of early onset preeclampsia - Agarwal, Shaily; Dwivedi, Divya; Gupta, Renu; Gupta, Garima; Lal, Pavika; Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is one of the most common complications in pregnancy and is a major cause of maternal and perinatal morbidity and mortality. Early prediction of preeclampsia is crucial in proactive management of the patient. Uric acid is a biomarker of hypertension. Methods: A prospective study was done on 200 pregnant females in their first or early second trimester of pregnancy and were followed till one week of delivery or termination of pregnancy. After taking socio-demographic details, detailed medical and obstetric history was taken. Blood pressure of the patients was routinely measured and mean arterial pressure was calculated. Blood and saliva samples were taken and were analysed following standard protocol for serum and salivary uric acid levels respectively. Participants were classified into normotensive and preeclampsia groups depending on the criteria met. Results: Preeclampsia group participants had significantly more adverse and feto-maternal outcomes. Salivary uric acid is a promising diagnostic predictor of preeclampsia in pregnant women by the virtue of being a non-invasive investigation with cut off value 4.86 mg/dl having a sensitivity of 70.8%, specificity of 45.7% and a PPV of 81.3%. Salivary uric acid level and mean arterial pressure were found to be better predictors of preeclampsia as compared to salivary uric acid level. Conclusions: Salivary uric acid is a reliable predictor of preeclampsia in pregnant females in first and early second trimester of pregnancy. Further largescale studies are warranted to establish an accurate cut off value with good diagnostic properties for Indian population.